Eosinophilic esophagitis - Jevtić, Jovan; Janković, Radmila (Medicinski podmladak, 2022)
Eosinophilic esophagitis (EoE) is an inflammatory disorder characterized by intraepithelial eosinophilic infiltration followed by esophageal dysfunction. Pathophysiological mechanism of EoE is not well understood yet, there are several factors that may contribute, such as host immunity, environmental and genetic factors. Modern diagnostic for EoE should include: esophageal dysfunction, esophageal biopsy with at least 15 eosinophils per high power field and absence of other pathology characterized by increased number of eosinophils. The most common presenting symptoms in adults are dysphagia, heartburn, food impaction and chest pain. Children are usually presented with nausea and vomiting, anorexia, heartburn, regurgitation, chest burn and abdominal pain. Endoscopically, patients with EoE are characterized by longitudinal furrows (vertical lines, darker than surrounding mucosa), esophageal trachealization (numerous transversal rings, as in trachea), exudate (white plaques), edema (decreased mucosal vascularization), strictures and crepe-paper mucosa (mucosal friability and tearing during endoscopy). Histological features of EoE could be separated into major and minor criteria. Major criteria include: intraepithelial infiltration by eosinophils (>15 eosinophils/HPF), eosinophilic microabscesses (≥ 4 eosinophils in a collection), eosinophils occupying outer layer of the squamous epithelium, epithelial sloughing and eosinophil degranulation. Minor criteria include: basal zone hyperplasia, lengthening of the epithelial papillae, intracellular edema and subepithelial fibrosis. In order to set adequate diagnosis, all other conditions related to increased number of eosinophils should be excluded. The most common and the most important differential is gastroesophageal reflux disease (GERD). Treatment of the EoE encompasses: proton pump inhibitors (PPI), corticosteroids (topical and systemic), elimination diet and esophageal dilation.